Phototherapy for hyperbilirubinaemia in very low birthweight infants. Issue 2 (February 1976) - Moncrieff, M W; Dunn, J
Abstract : Phototherapy was used to treat 20 newborn babies whose birthweight was below 1500 g and whose plasma bilirubin exceeded 8 mg/100 ml. The plasma bilirubin level was maintained below 13 mg/100 ml except in 4 babies whose level exceeded 13 mg/100 ml before treatment was started. In 60% of an untreated group of larger babies previously reported the plasma bilirubin level exceeded this figure. Phototherapy seems to control the plasma bilirubin level satisfactorily in very low birthweight infants, but frequent measurements on the second and third days of life are advised in order that treatment may be started promptly when it exceeds 8 mg/100 ml.